Making Sustainability Work Best Practices in Managing and Measuring Corporate Social, Environmental, and Economic Impacts - Epstein, Marc J.; Rejc, Adriana (Berrett-Koehler Publishers, 2014)
Now completely updated, Making Sustainability Work is the bible for applying real metrics and best practices to the often-nebulous realm of business sustainability. Mark Epstein and Adriana Rejc Buhovac provide concrete tools for measuring and increasing social and environmental impacts in a manner that businesses can understand and put to real use.